The Neo-Liberal Subjectivity of Native Culture in Diaspora Writing: A Sartorial Reading of the Unmarriageable by Soniah Kamal - Maria Batool; Hafsa Noor; Sara Anwar (Al-Qanṭara, 2023)
This study seeks to establish how women’s sartorial choices are subjected to both internal and external forces of oppression through the study of Unmarriageable by Soniah Kamal. Using postcolonial subjectivity to understand the convergence of vestigial structures of post-colonialism and a globalizing subjectivity, this paper challenges unified notions of national identity through the analysis of socio-cultural norms, dress, language and food in selected Anglophone Pakistani literature. It also unravels the ‘liminal spaces’ of destabilized identities and fragmented subjectivities that mark the postcolonial condition. Further, it illuminates the role of sartorial structures by incorporating Deleuze and Guattari’s conceptualization of ‘de-territorialisation and re-territorialisation’. Accordingly, globalization of everyday experiences makes it even more difficult to maintain a stable sense of local cultural identity, including national identity, as our daily life entwines itself more and more with the influences and experiences of a global world. In such conditions, the diaspora writers present the local sartorial culture as a conspicuous site of identity inscription, negotiation, and reinvention.